Characteristics of rice straw and its development as compost treated with natural nitrogen source. - Ali, Hassan Ibrahim; Ismail, Mohd Razi; Manan, Mohd Mokhtaruddin; Mohd Saud, Halimi (2001)
Rice straw utilization is one of the major problems facing rice farmers' world wide as well as Malaysia due to the high cost of collection, pollution emissions when burned and source of diseases when incorporated into the soil. However, composting is used as one of most effective means of alternative rice straw management This study was conducted to evaluate the characteristics of grinned rice straw and its development as compost treated with chicken manure as natural N source under humid conditions. The results indicated that rice straw has suitable physio-chemical characteristics that can be used as compost brown material. Composting process of rice straw treated with chicken manure (l:1) showed a typical temperature trend during composting, while moisture content increased and decreased at the end of the process. Moreover, electrical conductivity (EG) and pH increased, fluctuated and showed slight drop at the end of the composting process. Significant positive and negative correlations were obtained with total N%, carbon% and C/N ratio during days of composting. However, accumulation of nutrients and heavy metals significantly increased during composting which suggests a maturity of the product. On the other hand, physio-chemical characteristics of the finished compost were also examined.